2014
DOI: 10.2337/dc13-2644
|View full text |Cite
|
Sign up to set email alerts
|

Overnight Closed-Loop Insulin Delivery in Young People With Type 1 Diabetes: A Free-Living, Randomized Clinical Trial

Abstract: OBJECTIVETo evaluate feasibility, safety, and efficacy of overnight closed-loop insulin delivery in free-living youth with type 1 diabetes.RESEARCH DESIGN AND METHODSOvernight closed loop was evaluated at home by 16 pump-treated adolescents with type 1 diabetes aged 12–18 years. Over a 3-week period, overnight insulin delivery was directed by a closed-loop system, and on another 3-week period sensor-augmented therapy was applied. The order of interventions was random. The primary end point was time when adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 30 publications
6
134
0
3
Order By: Relevance
“…[12][13][14] This new study confirms the previous findings and adds two unique features: (1) a portable platform using a consumer electronics device (smartphone) to run the CLC system and all CGM, pump, and remote communications and (2) a control algorithm specifically designed to ''slide'' the patients' glucose levels to a target of 120 mg/dL at wakeup, thereby resetting their metabolic state overnight to near-normoglycemic morning BG levels, on consecutive nights. As a result, this study demonstrated not only significant improvement in overnight glucose control on CLC, but also significant improvement of patients' control on the next day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] This new study confirms the previous findings and adds two unique features: (1) a portable platform using a consumer electronics device (smartphone) to run the CLC system and all CGM, pump, and remote communications and (2) a control algorithm specifically designed to ''slide'' the patients' glucose levels to a target of 120 mg/dL at wakeup, thereby resetting their metabolic state overnight to near-normoglycemic morning BG levels, on consecutive nights. As a result, this study demonstrated not only significant improvement in overnight glucose control on CLC, but also significant improvement of patients' control on the next day.…”
Section: Discussionmentioning
confidence: 99%
“…9 The transition of CLC to a wearable outpatient system began in 2012 with the introduction of the Diabetes Assistant (DiAs)-the first wearable CLC system using a smartphone as a computational platform for its control algorithm. 10,11 Other recent trials confirmed the effectiveness of overnight CLC at diabetes camps for children 12 and at patients' homes, 13,14 placing laptop computers equipped with control algorithms at their patients' bedside.…”
mentioning
confidence: 94%
“…Depending on control algorithm and the population, mean overnight glucose is lower [29,31,34,36,38], similar [27,32,35,37] or slightly elevated [28,33] than during control therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised free-living overnight use of a MPC algorithm driven closed-loop in adolescents over a period of 3 weeks showed significant improvements in time spent within target range by a median 15 percentage points, reduced mean glucose by a mean 0.8 mmol/l, and reduced the number of nights with glucose readings below 3.5 mmol/l compared to sensor augmented pump therapy [38]. A slightly revised version of this closed-loop system was tested in the longest randomized home study in children and adolescents to date.…”
Section: Glucose Responsive Suspension Of Insulin Deliverymentioning
confidence: 99%
“…In recent years, BG control systems that maintain normoglycemia automatically by closed-loop continuous infusion of insulin have taken particularly large strides towards its commercial development. Some studies [3] already have had successful results for overnight freeliving conditions, whereas more recently there is focus on postprandial BG control [4] and its compliance with clinical guidelines considers patient input of the carbohydrate content of the meal. Nonetheless, BG control performance has been shown to be under-mined by consumption of high-fat mixed meal [5], thus revealing that not only glucose but also fatty acid metabolism is indispensable in the mathematical representation of postprandial glucose-insulin metabolism in T1DM.…”
Section: Introductionmentioning
confidence: 99%